2012
DOI: 10.1523/jneurosci.2814-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional Circuitry between Retrosplenial and Postrhinal Cortices during Fear Conditioning

Abstract: The retrosplenial (RSP) and postrhinal (POR) cortices are heavily interconnected with medial temporal lobe structures involved in learning and memory. Previous studies indicate that RSP and POR are necessary for contextual fear conditioning, but it remains unclear whether these regions contribute individually or instead work together as a functional circuit to modulate learning and/or memory. In Experiment 1, learning-related neuronal activity was assessed in RSP from home-cage, shock-only, context-only or fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 65 publications
7
32
0
1
Order By: Relevance
“…Therefore, this structure seems to be an important component of spatial circuits in both humans and rodents. Based on this evidence, it has been proposed that the RSC role in spatial navigation is due to either its ability to process the sequence of heading vectors required for navigating in space or its ability to support the transition between allocentric (world-centered) references, encoded by the hippocampus, and egocentric (selfcentered) references, supported by the parietal cortex (21).Recent studies suggested that, in addition to the hippocampus, other connected cortical regions can support encoding and storage of spatial memory (22)(23)(24)(25). Elevated expression of immediate early genes (IEGs) is thought to reflect this involvement (22,25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this structure seems to be an important component of spatial circuits in both humans and rodents. Based on this evidence, it has been proposed that the RSC role in spatial navigation is due to either its ability to process the sequence of heading vectors required for navigating in space or its ability to support the transition between allocentric (world-centered) references, encoded by the hippocampus, and egocentric (selfcentered) references, supported by the parietal cortex (21).Recent studies suggested that, in addition to the hippocampus, other connected cortical regions can support encoding and storage of spatial memory (22)(23)(24)(25). Elevated expression of immediate early genes (IEGs) is thought to reflect this involvement (22,25,26).…”
mentioning
confidence: 99%
“…Recent studies suggested that, in addition to the hippocampus, other connected cortical regions can support encoding and storage of spatial memory (22)(23)(24)(25). Elevated expression of immediate early genes (IEGs) is thought to reflect this involvement (22,25,26).…”
mentioning
confidence: 99%
“…Several lesion studies have involved RSC in memory (Sutherland et al 1988;Aggleton 2002, 2004;Harker and Whishaw 2004;Keene and Bucci 2008a,b,c;Dumont et al 2010;Haijima and Ichitani 2012;Robinson et al 2012). However, this kind of intervention has several drawbacks (Izquierdo and Medina 1998), including a lack of discrimination between memory acquisition, memory formation, or memory expression.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…However, the hippocampus does not exist nor act in isolation; cortical regions both within and outside of the medial temporal lobe provide critical sensory information to the hippocampal formation [5][6][7] . Traditional permanent lesion studies provide compelling evidence for the involvement of a number of cortical regions (e.g., the retrosplenial, postrhinal and entorhinal cortices) in hippocampal-dependent learning but are limited in their ability to discern the role of a particular region during discrete phases of learning [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%